2005
DOI: 10.1200/jco.2005.02.163
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and Continuous-Infusion Fluorouracil Versus Epirubicin, Cisplatin, and Fluorouracil for Advanced Gastric Adenocarcinoma: A Randomized Phase II Study

Abstract: DF can be safely given in an ambulant setting. Compared with ECF, the dual combination of DF shows promising efficacy and may be an alternative treatment option that avoids cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
66
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 19 publications
7
66
2
1
Order By: Relevance
“…All of these features are associated with decreased response rates to chemotherapy , Mai et al, 1999, Koizumi et al, 2000, Ajani et al, 2005). Yet despite these unfavourable baseline characteristics, the combination of docetaxel and S-1 conferred an ORR that was similar to those obtained with other combination regimens (Ajani et al, 2005;Thuss-Patience et al, 2005).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…All of these features are associated with decreased response rates to chemotherapy , Mai et al, 1999, Koizumi et al, 2000, Ajani et al, 2005). Yet despite these unfavourable baseline characteristics, the combination of docetaxel and S-1 conferred an ORR that was similar to those obtained with other combination regimens (Ajani et al, 2005;Thuss-Patience et al, 2005).…”
Section: Discussionsupporting
confidence: 53%
“…Although cross-study comparisons should be taken with caution, the survival effect observed in our study compares favourably with other chemotherapy regimens, such as docetaxel (6 -8 months Mai et al, 1999)) or S-1 (7 -8 months Koizumi et al, 2000)), or the combinations DC (11 months), DF (10 months), DCF (10 months), ECF (10 months) or FOLFOX-4 (11 months) (Ajani et al, 2005;De Vita et al, 2005;Thuss-Patience et al, 2005).…”
Section: Discussionsupporting
confidence: 51%
“…In addition to modifying the docetaxel schedule, both regimens involved an altered fluoropyrimidine schedule (either continuous-infusion 5FU or capecitabine) compared with 3-weekly TCF, which used a 4-day infusion of high-dose 5FU. This may also have contributed to lower rates of myelosuppression, as other studies have shown more manageable rates of haematological toxicities with protracted infusion schedules of 5FU (Thuss-Patience et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…In combination with CDDP, 5-FU or CDDP plus 5-FU or S-1, docetaxel has shown a higher ORR of 37 to 56% and MST of 9.0 to 14.3 months (Roth et al, 2000;Thuss-Patience et al, 2005;Van Cutsem et al, 2006;Yamaguchi et al, 2006).…”
mentioning
confidence: 99%